Brain natriuretic peptide levels predict 6-month mortality in patients with cardiogenic shock who were weaned off extracorporeal membrane oxygenation. Issue 29 (17th July 2020) - Kim, Hyoung Soo; Lee, Kyu Jin; Ha, Sang Ook; Han, Sang Jin; Park, Kyoung-Ha; Lee, Sun Hee; Hwang, Yong Il; Jang, Seung Hun; Park, Sunghoon
Abstract : Abstract: There are limited data regarding the association between brain natriuretic peptide (BNP) levels obtained after weaning from extracorporeal membrane oxygenation (ECMO) and the outcomes of patients with acute coronary syndrome (ACS)-associated cardiogenic shock. We prospectively obtained data regarding patients (aged ≥ 19 years) with ACS-associated cardiogenic shock who received ECMO and were subsequently weaned off the treatment. BNP levels were collected at 5 time points: pre-ECMO implantation, post-ECMO implantation, pre-ECMO weaning, day 1 after ECMO weaning, and day 5 after ECMO weaning. Of 48 patients with ACS-related cardiogenic shock, 33 were included in this analysis. Mean patient age was 59.0 (50.0–66.5) years, and 5 patients (15.2%) were women. Eight patients had asystole/pulseless electrical activity before ECMO and 14 (42.4%) had 3-vessel disease on coronary angiography. During the 6-month follow up, 12 (36.4%) patients died. BNP levels after ECMO weaning were significantly different between 6-month survivors and non-survivors. Cox proportional hazards model revealed that BNP levels (tertiles) on days 1 and 5 after ECMO weaning were significantly associated with 6-month mortality (hazard ratio, 7.872; 95% confidence interval, 1.870–32.756; 8.658 and 1.904–39.365, respectively). According to the Kaplan–Meier curves, the first tertile had significantly longer survival compared to the third tertile for both days 1 and 5 after ECMO weaning. Post-ECMO weaning BNP levels (days 1 and 5) were significantly associated with increased 6-month mortality in patients with ACS complicated by refractory cardiogenic shock who were weaned off ECMO. Abstract : Supplemental Digital Content is available in the text